Effects of the alpha antagonists and agonists injected into the lateral hypothalamus on the water and sodium intake induced by angiotensin II injection into the subfornical organ - Almeida, Nara Adriane Araújo [UNESP]; Antunes, Vagner Roberto [UNESP]; Saad, Wilson Abrão [UNESP]; De Arruda Camargo, Luiz Antonio [UNESP] (Elsevier, 1999)
The subfornical organ (SFO) and the lateral hypothalamus (LH) have been shown to be important for the central action of angiotensin II (ANG II) on water and salt regulation. Several anatomical findings have demonstrated neural connections between the SFO and the LH. The present experiments were conducted to investigate the role of the α-adrenergic antagonists and agonists injected into the LH on the water and salt intake elicited by injections of ANG II into the SFO. Prazosin (an α1-adrenergic antagonist) injected into the LH increased the salt ingestion, whereas yohimbine (an α2-adrenergic antagonist) and propranolol (a β-adrenergic antagonist) antagonized the salt ingestion induced by administration of ANG II into the SFO. Previous administration of clonidine (an α2-adrenergic agonist) or noradrenaline into the LH increased, whereas pretreatment with phenylephrine decreased the sodium intake induced by injection of ANG II into the SFO. Previous treatment with prazosin and propranolol reduced the water intake induced by ANG II. Phenylephrine increased the dipsogenic responses produced by ANG II, whereas previous treatment with clonidine injected into the LH reduced the water intake induced by ANG II administration into the SFO. The LH involvement with SFO on the excitatory and inhibitory mechanisms related to water and sodium intake is suggested.
Keywords: Adrenergic agonists; Adrenergic antagonists; Lateral hypothalamus; Sodium intake; Subfornical organ; Water intake; adrenalin; adrenergic receptor stimulating agent; prazosin; propranolol; yohimbine; animal experiment; drug effect; fluid balance; fluid intake; hypothalamus; male; nonhuman; priority journal; rat; sodium intake; subfornical organ; Adrenergic alpha-Agonists; Adrenergic alpha-Antagonists; Angiotensin II; Animals; Drinking; Hypothalamic Area, Lateral; Male; Rats; Rats, Sprague-Dawley; Receptors, Adrenergic, alpha; Sodium Chloride, Dietary; Subfornical Organ; Water-Electrolyte Balance